The credit risk of complex derivatives - Banks, Erik. (Basingstoke : Macmillan, 1997)
Derivatives and risk. The credit risk of complex options. The credit risk of complex swaps. The credit risk management of derivative exposures.
Keywords: Finance; Economics; Foreign exchange; Banks; Risk management; Foreign exchange futures; Derivative securities